Patient Engagement and Self-Efficacy Effects on Quality of Life,the Mediating Role of Accessibility - Aulia Putri Evindra; Kemala Rita; Sandra Dewi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Chronic Kidney Disease (CKD) is a growing global health concern that significantly affects patients’ quality of life. At Bhakti Asih General Hospital, Tangerang, the number of hemodialysis patients increased by 20.42% and dialysis procedures by 25.06% between 2023 and 2024. Despite this service expansion, preliminary findings revealed that 32% of patients reported poor quality of life, 31% experienced low engagement in care, 34% demonstrated low self-efficacy particularly in dietary and fluid management and 32% faced accessibility barriers. These findings indicate a gap between increased service volume and patient-centered outcomes. This study aimed to analyze the effects of patient engagement and self-efficacy on the quality of life of hemodialysis patients, with healthcare accessibility as a mediating variable. A quantitative cross-sectional design was employed. Active hemodialysis patients were selected using purposive sampling. Data were collected through structured questionnaires and analyzed using Structural Equation Modeling (SEM).The results demonstrated that patient engagement and self-efficacy had significant positive effects on quality of life, both directly and indirectly through accessibility. Accessibility also significantly influenced quality of life and strengthened the relationships between patient engagement, self-efficacy, and quality of life.These findings highlight the importance of integrating patient engagement strategies, strengthening self-efficacy through education, and improving service accessibility to enhance quality of life among hemodialysis patients